Inovação orientada pelo design e a proposta de valor - Marin, Júlia Carolina (Universidade do Vale do Rio dos Sinos, 2015)
The article aims to understand the different aspects of the relationship between innovation and value proposition. To this end, we sought theoretical academic papers in foreign and national, in order support the subject, and, after that, we applied the acquired knowledge in a case study of Pandorga store. This was conducted through observation and document research, as well as interviews with founders, customers, suppliers and partners.
Keywords: Design; Valor; Inovação; Transformadora; Radical; Value; Innovation; Transformational